050 Western blot analysis of KPNA4 and its relevance to nucleocytoplasmic transport dysfunction in ALS/FTD. Issue 12 (14th November 2019) - Zatorska, Anna; Solomon, Daniel; Hortobagyi, Tibor; Hirth, Frank
Abstract : ALS and FTD are progressive neurodegenerative diseases, often characterised by cytoplasmic aggregation of TDP-43. Nuclear import of TDP-43 occurs via the classical pathway in which karyopherin alphas (KPNAs) act as adaptor proteins. KPNA4 has been identified as the strongest interactor of TDP-43, and karyopherins co-localise with the aberrant cytoplasmic aggregates in ALS/FTD. This study explored how KPNA4 is affected in the spinal cord of sporadic-ALS (n=8), C9ORF72-ALS cases (n=7) as compared to control (n=6) and in the frontal cortex of sporadic-FTD (n=8), C9ORF72-FTD (n=8), and Tau-FTD (n=8) as compared to control (n=8). Quantitative western blotting was used to analyse whether KPNA4 differed between the protein samples from post-mortem tissue. Soluble levels of KPNA4 were significantly lower in the spinal cord of sporadic-ALS patients compared to control (D=0.4321, CI= 0.124–0.7401, p=0.0086), in the frontal cortex of sporadic-FTD patients compared to control (D=0.258, 95% CI=0.065–0452, p= 0.01) and in the frontal cortex of Tau-FTD patients compared to control (D= 0.22, CI= 0.03–0.42, p= 0.022) but not in C9ORF72 ALS/FTD. The results show a statistically significant downregulation of KPNA4 in sporadic ALS/FTD and Tau-FTD, suggesting KPNA4 could be forming insoluble aggregates or that the translation of KPNA4 mRNA may be reduced.